Kualitas Pupuk Organik Feses Ternak Kombinasi Limbah Buah Untuk Mendukung Pertumbuhan Rumput Gajah: Organic Fertilizers Contained Animal Faeces and Fruit Waste Mixture for Supporting Elephant Grass Growth - Lestari, Rika; Amaliah, R; Juanda; Jusri (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2023)
This research was conducted to determine the nutrient content of organic fertilizers (livestock feces combined with fruit waste) and its application to elephant grass. The experiment used a completely randomized design (CRD) with 5 treatments and 4 replicates. P0 = elephant grass (control), P1 = elephant grass + (rabbit faeces and fruits waste (RFAWF) 200g/polybag, P2 = elephant grass + goat feces and (fruits waste) 200g/polybag, P3 = elephant grass + cow feces and fruits waste 200g/polybag dan P4 = elephant grass + buffalo feces and fruits waste 200g/polybag. The research results showed that nutrient content of organic fertilizer (pH, C-organic, total N, P2O5, K2O, moisture content) was in accordance with SNI for rabbit feces and cow feces. The fresh weight and dry weight of elephant grass biomass was not significantly affected by treatment. Organic fertilizers containing animal feces and fruit waste mixture effectively increases biomass production compared to control. It was concluded that the best combination of fertilizer is resulted from goat feces and mixture of fruit waste (banana peel, pineapple peel and papaya peel) is compared to other feces. Key words: C/N ratio, elephant grass, fruits waste, organic fertilizer